Mathematical approach to pollutant transport through ground water / G. Jagmohan Das - G., Jagmohan Das (Universiti Teknologi MARA, Sarawak, 2001)
This article deals with the mathematical approach to the analysis of pollutant transport through the porous medium. Different processes involved in the transport phenomena are explained. A partial differential equation representing all these processes, along with the initial and boundary conditions for a two-layered aquifer is formulated. A case study is presented to illustrate the application of Finite Element based algorithm and the computer software already developed. The results of the numerical experiments conducted to trace the spreading of pollutant with time, are presented in the form of contour curves. The investigations are extended to estimate the refreshing time of the aquifer system.